2004
DOI: 10.1002/syn.20089
|View full text |Cite
|
Sign up to set email alerts
|

Selective alterations of gene expression in mice induced by MPTP

Abstract: 1-methyl-4-phenyl-1,2,4,6,-tetrahydropyridine (MPTP) is a selective neurotoxin that produces striatal dopamine depletion resulting in parkinsonism like symptoms in humans and is, therefore, used to generate animal models for Parkinson's disease (PD). In this study, C57BL/6N mice were treated with MPTP acutely (3x20 mg/kg, 2-hour interval, one day injection). Mice were then sacrificed 24 hours after the last injection and brain tissue was collected for analysis. Significant decrease of striatal dopamine (DA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…MPTP did not alter ␤-actin expression under the dosing conditions used in our study either by qWB or immunohistochemical determinations. Similarly, other studies have found that MPTP does not alter ␤-actin mRNA or protein (Miller et al, 2004;Xu et al, 2005). Despite these observations, it is important to note that choice of an 'unaffected' marker for normalization may be confounded by reduced protein expression secondary to neurodegeneration.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…MPTP did not alter ␤-actin expression under the dosing conditions used in our study either by qWB or immunohistochemical determinations. Similarly, other studies have found that MPTP does not alter ␤-actin mRNA or protein (Miller et al, 2004;Xu et al, 2005). Despite these observations, it is important to note that choice of an 'unaffected' marker for normalization may be confounded by reduced protein expression secondary to neurodegeneration.…”
Section: Discussionmentioning
confidence: 91%
“…Changes in gene expression in the midbrain and in SN neurons captured from brains of MPTP treated animals have been reported using RT-PCR (Chung et al, 2005;Kuhn et al, 2003;Xu et al, 2005). However, it is unknown how changes in gene transcripts translate to changes in protein expression and changes in gene expression have not yet been correlated to functional or pathologic outcome.…”
Section: Introductionmentioning
confidence: 95%
“…One chronic regimen utilizes repeated treatments over 5 weeks and requires the co-administration of the adjuvant probenecid to retard the renal clearance of the toxic metabolites of MPTP [73,95]. For all these protocols, SN TH immunoreactive neurons disappear rapidly, but this loss may not reflect actual DA cell death if neurons are counted shortly after treatment, since MPTP down-regulates TH gene expression [134]. In the past few years, the introduction of unbiased stereology to count the THimmunoreactive and the Nissl-stained neurons at least 7 days following any MPTP treatment has provided better estimates of DA cell loss for these models.…”
Section: Pd Models: Acute or Chronic Delivery Of Neurotoxicantsmentioning
confidence: 99%
“…Chronic administration of MPTP produces a dosedependent decrease in striatal DA concentration, and a corresponding loss of striatal vesicular monoamine transporter (VMAT-2) protein in wild-type mice (Drolet et al, 2004;Xu et al, 2004). The MPTP-treated primate responds to the administration of L-DOPA and other antiparkinsonian drugs providing a model to study the mechanism of dopaminergic degeneration, to test new drugs and studies on locomotor activity (Jenner and Marsden, 1986;Gerlach et al 1991;Archer et al, 2003).…”
Section: Mptpmentioning
confidence: 96%